Synthesis and spectral properties of new fluorescent hydrazone disperse dyes and their dyeing application on polyester fabrics. Issue 8 (August 2019) - Aysha, Tarek; Zain, Mostafa; Arief, Mohamed; Youssef, Yehya
Abstract: A new series of solid state fluorescent disperse dyes based on hybrid structure of pyrrolinone ester (PES)/coumarin moiety was prepared and fully characterized using spectroscopic analysis such as 1 HNMR, MS and IR spectra. The coumarin derivative (7- amino-4- methyl coumarin) was initially prepared from amino phenol via multi steps condensation reactions and its diazonium salt coupled with the pyrrolinone ester to form the hydrazone dyes. 1 HNMR data of the prepared dyes exhibited a pure hydrazone form as a mixture of E, Z isomers. These dyes showing a significant emission in solid state as well as on the dyed fabric. The dyeing application on polyester fabrics was investigated which showing that these dyes show high affinity to polyester fabric, and minor change in the dye affinity by changing pH even under alkaline conditions was observed.